Cascade covalent and coordination bond formation for Ti-based cage assembly: catalysis and coordination bifunctionality of TiCl4. Issue 10 (12th February 2018) - Tong, Jing; Xu, Tingting; Liu, Shengjun; Zhang, Junxiang; Hou, Xudong; Liu, Bo
Abstract : Ti-based cage of [Ti4 O2 L4 Cl8 ] (L = 4-acetamidobenzoic acid) is synthesized by a one-pot solvothermal reaction of the 4-aminobenzoic acid, acetic acid and TiCl4 . Ti(iv ) ion functions as a Lewis acid catalyst and coordination sites to afford Ti-based cage formation in a cascade fashion. Abstract : The metallosupramolecular Ti-based M4 L4 cage of [Ti4 O2 L4 Cl8 ] (L = 4-acetamidobenzoic acid) is synthesized via the one-pot solvothermal reaction of 4-aminobenzoic acid, acetic acid and TiCl4 . The Ti(iv ) ion functions as a Lewis acid catalyst for acylation condensation, and then coordinates with the resultant 4-acetamidobenzoic acid to afford Ti-based cage formation in a cascade fashion.